PELAYANAN PERNIKAHAN DI KABUPATEN NUNUKAN: ANTARA MENGATASI KETERBATASAN DAN MENJAGA KEMASLAHATAN - Kustini Kustini; Wahidah R. Bulan (Harmoni, 2015)
Religious services specially marriage service in border areas address complicated problems. Those problems are insisted to be solved and services increase sharply because the legality of marriage implies to social problems such as making civil registration document (birth certificate, family register document, and passport extension), letter of inheritance, separation of marriage, and so on. The purposes of this study are to describe religious affair office (KUA) condition, identify problems faced KUA in giving marriage service, recognize strategies to solve the problems and factors that stimulate them. This study uses qualitative approach with some instruments such as interview, observation, FGD, and literature study. The study taking place in Nunukan and Sebatik islands shows that many problems related to marriage services in border area are found such as administrative registry procedure, infrastructure and service structure restriction, and religious value building (syariat Islam). Stakeholders must involve dealing with those problems and all citizens have to build their awareness that they are not passive service receivers.